2006
DOI: 10.1161/circulationaha.105.567107
|View full text |Cite
|
Sign up to set email alerts
|

Increased Small Low-Density Lipoprotein Particle Number

Abstract: Background-Levels of LDL cholesterol (LDL-C) are frequently not elevated in individuals with the metabolic syndrome (MetSyn). However, the atherogenic potential of LDL may depend on the number and size of LDL particles in addition to the cholesterol content of LDL. Methods and Results-We examined the sex-specific cross-sectional relations of small LDL particle number (determined by nuclear magnetic resonance spectroscopy) to the presence of MetSyn and its components in 2993 Framingham Heart Study participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
2
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(111 citation statements)
references
References 44 publications
(28 reference statements)
5
101
2
3
Order By: Relevance
“…Thus, people with a small mean LDL particle size have relatively more small LDL particles as compared with people with a large mean LDL particle sizes. Small LDL particle sizes are associated with type II diabetes (Festa et al 2005), metabolic syndrome (Gentile et al 2008;Kathiresan et al 2006), insulin resistance (Garvey et al 2003;Goff et al 2005), incident CVD (Mora et al 2009), and future CAD (El Harchaoui et al 2007). Possible atherosclerosis could be induced by those small LDL particles, as indicated in a study of two knockout mice strains with similar cholesterol levels, were the Ldr −/− Apob 100/100 mice had a larger number (Veniant et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, people with a small mean LDL particle size have relatively more small LDL particles as compared with people with a large mean LDL particle sizes. Small LDL particle sizes are associated with type II diabetes (Festa et al 2005), metabolic syndrome (Gentile et al 2008;Kathiresan et al 2006), insulin resistance (Garvey et al 2003;Goff et al 2005), incident CVD (Mora et al 2009), and future CAD (El Harchaoui et al 2007). Possible atherosclerosis could be induced by those small LDL particles, as indicated in a study of two knockout mice strains with similar cholesterol levels, were the Ldr −/− Apob 100/100 mice had a larger number (Veniant et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In MS, the mechanism for sdLDL formation is known to be related to IR and hypertriglyceridemia; this relationship was demonstrated in the Framingham Heart study. 18 Diabetes, MS, and IR all have associated atherogenic lipids, including a predominance of sdLDL, lower HDL cholesterol, and higher TG levels. [26][27][28] Goff et al 29 reported that IR was associated with increased numbers of sdLDL particles in the Insulin Resistance Atherosclerosis Study.…”
Section: Resultsmentioning
confidence: 99%
“…30 Most of these conditions are frequently associated with HTN, but the exact role of HTN in sdLDL formation is still obscure. Systolic blood pressure and DBP were significantly correlated with small LDL particle numbers in patients with MS. 18 Several studies reported the association of HTN with an elevation of sdLDL levels. Landray et al 31 reported a preponderance of smaller LDL subfractions in patients with untreated HTN, but the study population did not completely exclude patients with MS or hypertriglyceridemia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations